Effect of cupping therapy versus moderate-intensity aerobic exercise on the lipid profile in women with diabetes - Ahmed Elnaggar, Moustafa Ibrahim; Alkholy, Wessam Ali; Atallah Ahmed Zaid, Alyaa Abdallah; Mazen, Mohamed Mohamed; Abo Sabee Sherif, Mai Mahmoud Abo Sabee; Mahmoud, Tarek H.; Zaky, Entesar Hussein (SPORT TK-EuroAmerican Journal of Sport Sciences, 2026)
This study aimed to find out the effect of wet cupping versus moderate-intensity aerobic exercise on lipid profile and blood sugar in diabetic obese women. Sixty diabetic women took part in this study; their ages ranged from 40 to 60 years, and their Body Mass Index (BMI) ranged from 30 to 34.9 kg/m². They were randomly allocated into two groups; group A received medication and moderate aerobic exercise three times per week for eight weeks, and group B received medication and wet cupping two times at two months. Triglycerides, cholesterol, LDL cholesterol, and HDL cholesterol were measured before and after eight weeks at the end of the study. The study demonstrated a statistically significant reduction in the triglyceride levels (p<0.01). Total cholesterol (p<0.01) and LDL (p<0.05) levels decreased significantly in both groups. HDL levels increased significantly in Group A (p<0.01), whereas no significant increase was observed in Group B (p>0.05). It was that aerobic exercise was more effective than wet cupping therapy on the lipid profile in diabetic women.